The Comparison of Lexical Collocations in English Textbooks Used in Indonesia - Ifadloh, Nur; Warsono, Warsono; Faridi, Abdurrahman (Universitas Negeri Semarang, 2021)
Teaching collocations becomes very important for ESL/EFL students to achieve language fluency since the students spend a great amount of time interacting with their textbooks. This study aims to investigate the comparison of lexical collocations used in two textbooks used regularly in senior high school level in Semarang namely Aim High Student’s Book 1 and Bahasa Inggris Kelas X. This study applied descriptive qualitative method. The documentary method was used in collecting the data. The data were analyzed based on collocation theories proposed by Benson, et al. (1997) and Lea (2002). The result showed that there were three similarities found regarding the lexical collocation occurrence in all parts of the textbooks, the highest frequency of the lexical collocations occurrence in the exercise part of the textbooks, and the highest frequency of the types of lexical collocations in the textbooks. Meanwhile, there are three differences found regarding the number of lexical collocation frequency in each textbook, the order in using lexical collocations from the highest to the lowest frequency, and the way the authors of the textbooks in introducing and teaching lexical collocations to the students. Furthermore, it was also found that Bahasa Inggris Kelas X produced some inaccurate lexical collocations.